Staining clinical specimens for acid-fast bacilli by means of a mechanical conveyor system. Issue 2 (February 1978) - Heimer, G V; Joseph, N; Taylor, C E
Abstract : A Cyto-Tek staining machine designed for Papanicolau staining of cervical smears has been adapted for auramine staining of smears of sputum and other clinical specimens for acid-fast bacilli. The results compared favourably with those obtained by a manual method of staining. Contamination of negative smears by acid-fast bacilli from positive smears was not found. Since this study the machine has continued to be in routine use with a considerable saving in labour.